Comparação dos sinais vitais e concentração de monóxido de carbono no ar exalado entre fumantes passivos e não fumantes - Silva, Berta Lúcia Mendonça [UNESP]; Ramos, Dionei [UNESP]; Freire, Ana Paula Coelho Figueira [UNESP]; Uzeloto, Juliana Souza [UNESP]; Previatto, Mariana Belon [UNESP]; Leal, Alice Cristine de Souza [UNESP]; Ramos, Ercy Mara Cipulo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Introduction: Exposure to cigarette smoke can cause serious damage to the health of smokers. But little is known about the effects of tobacco smoke on passive smokers. Objective: To compare vital signs and carbon monoxide concentration in exhaled air of passive smokers and individuals that are not exposed to cigarette smoke regularly. Material and Methods: We included in the study 57 subjects divided into two groups: passive smokers (PG) and no smoking (CG). Were collected carbon monoxide concentration in exhaled air (COex) and vital signs. Were the data analyzed by statistical programme GraphPadPrism®. To assess the normality of the data was held the Shapiro-Wilk test. For a comparison between groups was used the t test student. The level of significance was set at p<0.05. Results and Discussion: Participants in the PG and CG had a mean age of 43.97±9.60 and 41.45±6.94 years and 27.91±BMI of 4.79 and 28.40±5.77 kg/m2 , respectively. As for vital signs , the PG and GC showed SBP 121.8±17.01 and 112.4±10.12 mmHg (p=0.02), PAD 76.43±12.54 and 74.8±10.46 mmHg (p=0.70), FC 72.68±15.38 and 77.56±10,79 bpm and (p=0.35), f 17.71±2.42 and 17±2.77 ipm (p=0.26), SpO2 97.68±1.25 and 97.6±1.08 % (p=0.66) and COex 2.14±2.41 and 2.96± 2.95 ppm (p=0.19), respectively. Conclusions: We conclude from this study that passive smokers, have higher values in systolic blood pressure when compared to individuals who are not exposed to tobacco smoke.

Introdução: A exposição à fumaça do cigarro pode ocasionar prejuízos graves à saúde do tabagista. Porém pouco se sabe sobre os efeitos da fumaça do tabaco em tabagistas passivos. Objetivo: Comparar sinais vitais e concentração de monóxido de carbono no ar exalado de fumantes passivos e indivíduos que não são expostos à fumaça do cigarro regularmente. Material e Métodos: Fizeram parte do estudo 57 indivíduos divididos em dois grupos: tabagistas passivos (GP) e controle (não fumantes) (GC). Foram coletados sinais vitais e monóxido de carbono (COex). Os dados foram analisados pelo programa estatístico GraphPadPrism®. Para avaliar a normalidade dos dados foi realizado o teste de Shapiro-Wilk. Para a comparação entre os grupos foi utilizado o teste t de student. O nível de significância utilizado foi de p<0,05. Resultados e Discussão: Os participantes do GP e GC apresentaram média de idade de 43,97±9,60 e 41,45±6,94 anos e IMC de 27,91±4,79 e 28,40±5,77 Kg/m2 , respectivamente. Quanto aos sinais vitais, o GP e GC apresentaram PAS de 121,8±17,01 e 112,4±10,12 mmHg (p=0,02), PAD de 76,43±12,54 e 74,8±10,46 mmHg (p=0,70), FC de 72,68±15,38 e 77,56±10,79 bpm (p=0,35), f de 17,71±2,42 e 17±2,77 ipm (p=0,26), SpO2 de 97,68±1,25 e 97,6±1,08 % (p=0,66) e COex de 2,14±2,41 e 2,96±2,95 ppm (p=0,19), respectivamente. Conclusões: Conclui-se com este estudo que tabagistas passivos, apresentam valores mais elevados na pressão arterial sistólica quando comparados a indivíduos que não são expostos à fumaça do tabaco.
Keywords: Tobacco; Vital signs; Tabaco; Sinais vitais